First Amendment institutions - Horwitz, Paul. (Cambridge, Mass. : Harvard University Press, 2013)
Addressing a host of hot-button issues, from the barring of Christian student groups and military recruiters from law schools and universities to churches' immunity from civil rights legislation in hiring and firing ministers, Paul Horwitz proposes a radical reformation of First Amendment law. Arguing that rigidly doctrinal approaches can't account for messy, real-world situations, he suggests that the courts loosen their reins and let those institutions with a stake in First Amendment freedoms do more of the work of enforcing them. Universities, the press, libraries, churches, and various other institutions and associations are a fundamental part of the infrastructure of public discourse. Rather than subject them to ill-fitting, top-down rules and legal categories, courts should make them partners in shaping public discourse and First Amendment law, giving these institutions substantial autonomy to regulate their own affairs. Self-regulation and public criticism should be the key restraints on these institutions, not judicial fiat. Horwitz suggests that this approach would help the law enhance the contribution of our "First Amendment institutions" to social and political life. It would also move us toward a conception of the state as a participating member of our social framework, rather than a reigning and often overbearing sovereign. First Amendment Institutions offers a new vantage point from which to evaluate ongoing debates over topics ranging from campaign finance reform to campus hate speech and affirmative action in higher education. This book promises to promote--and provoke--important new discussions about the shape and future of the First Amendment
Addressing a host of hot-button issues, Horwitz argues that rigidly doctrinal interpretation renders First Amendment law inept in the face of messy, real-world situations. Courts should let institutions with a stake in these freedoms do more work to enforce them. Self-regulation and public criticism should be the key restraints, not judicial fiat.
The conventional First Amendment -- The lures and snares of acontextuality -- Taking the institutional turn -- Institutions and institutionalism -- Where ideas begin : universities and schools -- Where information is gathered : the press, old and new -- Where souls are saved : churches -- Where ideas reside : libraries -- Where ideas meet : associations -- The borderlands of institutionalism -- Critiques of First Amendment institutionalism -- Beyond the institutional turn.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
In English.
Keywords: United States; Constitution (United States); Freedom of speech -- United States; Freedom of the press -- United States; Freedom of religion -- United States; Assembly, Right of -- United States; Liberté d'expression -- États-Unis.; Liberté de la presse -- États-Unis.; Liberté religieuse -- États-Unis.; Liberté de réunion -- États-Unis.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; PHILOSOPHY -- Political; Assembly, Right of; Freedom of religion; Freedom of speech; Freedom of the press; United States